Experimental Study on the Characteristics of Granular Materials’ Flows and Fractures under Uniaxial Compression - Futian Zhao; Jun Liu; Zhimin Xiao; Mingqing Liu; Yue Wang; Chen Ou; Mengyang Zhen (Advances in Civil Engineering)
The mechanical behaviors of granular materials have high complexity. Since the mechanical behaviors of granular materials are difficult to describe theoretically, in this paper, the flow and fracture characteristics of granular materials were discussed by the experimental method. An experimental method was firstly proposed to identify the mechanical behaviors of granular materials under extra loading. An experimental device, which can be used to monitor force and displacement between particles, was invented. The uniaxial compression experiments of granular particles with different materials and grades were carried out, and the overall and local force between particles was obtained and investigated. Due to the flow of particles, the overall force rises in a fluctuating manner and the local force is not distributed evenly. Then, the particle fragments were sieved layer by layer. It was confirmed that the particles and loading strength have great influences on fractures of granular materials.